Language Style in thejakartapost.com - Priyadi, Dwiyanto Haris (Language Horizon: Journal of Language Studies, 2021)
Language is one of the important communication tools for communicating with other people. Language can be found in both spoken and written forms. One form of language implementation in writing can be found in online news portal newspapers. In each writing there is a writing style. The writing style itself becomes something unique in each person’s writing. One use of writing style can also be found in the news on thejakartapost.com which discusses the banning of Huawei by the United States government published on May 16, 2019 to May 23, 2019. The purpose of this study is to find out what elements of style that are used in the news and what classification of style that is used in the news. The research subjects in this study were news about the ban on Huawei products by the United States government by thejakartapost.com published on May 16, 2019 to May 23, 2019. There were 3 news items selected and researched by the researcher. This study uses the theory of writing style by Seyler and Joss to examine the data under study. The researcher found that there were 38 simple sentences, 11 compound sentences, 12 complex sentences, 16 connotative words, and 25 quotes. These three stories are neutral in tone because the authors only convey the facts of what happened between the United States government and the Huawei company. The writing style contained in the three news stories is formal due to the choice of words used by the news writers.